Mangrove Forests: Natural Laboratories for Studying Epigenetic and Climate Changes - Miryeganeh, Matin (Frontiers in Plant Science, 2022)
In the adaptation market, plants cash in the changes of their DNA (either genetic or epigenetic) to purchase fitness. Fitness is negatively affected by stressful conditions caused by climate change and well-designed studies are required to investigate the fine-tuning cooperation of epigenetic and genetic changes in response to those stresses. Mangrove trees are promising model systems for studying climate change because the effects of environmental changes are already evident in their natural habitats where they are exposed to different salinity levels ranging from saltwater to freshwater. In addition, as mangrove species are known to have very low genetic diversity caused by their stressful living conditions, epigenetic variation is likely to be a vital source for them to response to environmental changes. This mini review aims to provide an overview of available studies on epigenetic regulation and adaptation of mangroves.